Morphological constraint in a hyperdiverse lineage of neotropical tetras: a Geometric Morphometric analysis of three subfamilies of Acestrorhamphidae (Teleostei: Characiformes) - Bernal, Volnys Kenzo [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
The order Characiformes represents one of the most morphologically and taxonomically diverse clades of Neotropical freshwater fishes. Within this group, the recently delimited family Acestrorhamphidae exhibits high species richness, yet previous studies have shown that its members display highly conserved morphology. This poses a significant challenge for ichthyological systematics and raises questions about the evolutionary processes underlying such a pattern. This study investigates the influence of intrinsic factors on morphological evolution and establishes a temporally calibrated phylogenetic framework for analyses of integration and modularity. A total of 32 species from three subfamilies: Pristellinae, Stethaprioninae, and one currently unnamed subfamily were analyzed. Using geometric morphometric techniques, we sought to quantify morphological variation and covariation within the group; test hypotheses of morphological modularity and integration based on functional and phylogenetic criteria; and assess how these patterns influence the evolvability and morphological disparity of a group characterized by high taxonomic diversity but low apparent morphological variation. We tested multiple modularity hypotheses under the null model of no modular structure, including a two-module configuration separating cranial and postcranial regions, and a three-module configuration comprising cranial, postcranial, and caudal modules. Notably, the caudal module consistently displayed greater independence than the cranial and postcranial modules, even after accounting for phylogeny. The high degree of morphological integration observed suggests that the body evolves as a cohesive functional unit, limiting independent variation between anatomical regions. This strong coordination among body parts acts as an intrinsic constraint on morphological change, channeling evolution along specific trajectories, particularly those related to hydrodynamics and foraging. However, it does not prevent the emergence of diversity; on the contrary, it may shape how such diversity arises. These findings complement ecological and paleobiogeographic studies seeking to understand how diversity originates and is maintained.

A ordem Characiformes, um dos grupos mais diversos de peixes de água doce neotropicais, abriga a família Acestrorhamphidae — recentemente delimitada — que, apesar da alta riqueza de espécies, apresenta morfologia conservada, o que dificulta sua sistemática e levanta questionamentos sobre os processos evolutivos envolvidos. Este estudo aborda fatores intrínsecos que influenciam a evolução morfológica do grupo, utilizando um contexto filogenético calibrado temporalmente e técnicas de morfometria geométrica para investigar padrões de integração e modularidade em três subfamílias: Pristellinae, Stethaprioninae e uma ainda não nomeada. Foram testadas hipóteses baseadas em critérios funcionais e filogenéticos, revelando que a hipótese de três módulos (cranial, pós-cranial e caudal) obteve maior suporte estatístico. A modularidade mostrou-se mais evidente na ausência da filogenia, sugerindo que estruturas morfológicas intrínsecas não são totalmente explicadas pela história evolutiva, enquanto a integração morfológica teve correlações mais altas com o uso da filogenia, evidenciando a influência da herança comum. O módulo caudal destacou-se por maior independência, e a forte integração morfológica observada indica que o corpo evolui como uma unidade funcional coesa, o que restringe a variação independente entre regiões anatômicas. Essa coordenação atua como fator limitante, canalizando a evolução para trajetórias específicas ligadas à hidrodinâmica e forrageamento, sem impedir a emergência da diversidade, podendo inclusive moldá-la. Tais achados dialogam com abordagens ecológicas e paleobiogeográficas na tentativa de compreender a origem e manutenção da diversidade no grupo.
Restrição morfológica em uma linhagem hiperdiversa de tetras neotropicais: uma análise de morfometria geométrica de três subfamílias de Acestrorhamphidae (Teleostei: Characiformes)
Keywords: Neotropical; Diversification; Geometric morphometrics; Evolution; Morphology; Diversificação; Morfologia; Evolução; Peixes neotropicais; Morfometria neométrica